Evaluation of some definite integrals through arctangent function and infinite products - Ramesh Kumar Muthumalai (Scientia, 2025)
Some integrals involving elementary functions and special functions such as exponential integral, psi function, etc., are evaluated through arctangent function, infinite series and infinite products.